UWAGI DO WYKŁADNI ART. 19 UST. 1 USTAWY O KINEMATOGRAFII - Stanik, Mariusz (Zeszyty Prawnicze, 2016)
Comments to the Interpretation of art. 19 Clause 1 of the Cinematography Act Summary The text describes a dispute between entities conducting cinemas and film distributors regarding the interpretation of art. 19 clause 1 of the Cinematography Act. The dispute concerned the question whether under the aforementioned provision film distributors are obliged to participate in financing the fee towards Polish Film Art Institute. Analysis of this issue is based on the Warsaw District Court and Appeal Court judgments issued in 2008 and 2009. Analysis also takes into consideration the stenographic records of the parliamentary committee working under the Cinematography Act and interpretation of art. 19 clause 1 of the Cinematography Act made by Polish Film Art Institute itself. In conclusion the author states that according to art. 19 clause 1 of the Cinematography Act the only entities obliged to finance and pay the fee towards Polish Film Art Institute are entities conducting cinemas. Possible changes in this scope may be made only under the appropriate provisions of civil law agreements between such entity and film distributor.